Defend ID's Strategic Management to be in The Top 50 Defense Global Company: SWOT Analysis of PT Dahana - Nurman Machmud; Hikmat Zakky Almubaroq; Aris Sarjito (CV. AFDIFAL MAJU BERKAH, 2024)
A Defence SOE Holding was formed called Defence Industry Indonesia (Defend ID) and PT Dahana (Persero) is one of the 4 (four) companies incorporated in this holding. To achieve Defend ID's target of becoming a Top 50 Defence Global Company, PT Dahana implements strategic management to increase its competitiveness and become a major player in the global defence industry. PT Dahana faces strategic challenges in the defence industry both at the internal, national and global levels. This research article uses a qualitative method with a SWOT (Strengths, Weaknesses, Opportunities and Threats) framework, with the aim of obtaining a systematic assessment of PT Dahana's internal and external strategic factors. The research results obtained are that PT Dahana can utilize its strengths to overcome weaknesses and threats and take advantage of existing opportunities. By continuously strengthening strategies and innovations, PT Dahana is expected to continue to maintain and improve its position in the future.